2005
DOI: 10.1002/ptr.1682
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted:Matrix metalloproteinase-1 expression inhibitory compound from the whole plants ofViola ibukiana Makino

Abstract: Bioassay-guided fractionation has led to the isolation of two triterpenoid saponins 3-O-[O-beta-D-glucopyranosyl-(1 --> 3)-O-beta-D-glucopyranosyl] oleanolic acid (1), and 3-O-[O-beta-D-glucopyranosyl-(1 --> 2)-O-beta-D-glucopyranosyl] oleanolic acid (2) from the whole plants of Viola ibukiana Makino. Compound 2 showed matrix metalloproteinase-1 expression inhibition activities in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…87 Triterpenoid saponins 3-O-[O-beta-d-glucopyranosyl-(1→2)-O-beta-d-glucopyranosyl] oleanolic acid from the whole plants of Viola ibukiana Makino showed MMP-1 expression inhibition activities in a dose-dependent manner. 88 Two plant MMPs purified from soybean (Glycine max) leaves 89 and buckwheat (Fagopyrum esculentum) seeds 90 have been characterized. Evidence indicated that GmMMP2 may play a role in a novel defense mechanism in plants against pathogenic infections.…”
Section: Mmps In Plantsmentioning
confidence: 99%
“…87 Triterpenoid saponins 3-O-[O-beta-d-glucopyranosyl-(1→2)-O-beta-d-glucopyranosyl] oleanolic acid from the whole plants of Viola ibukiana Makino showed MMP-1 expression inhibition activities in a dose-dependent manner. 88 Two plant MMPs purified from soybean (Glycine max) leaves 89 and buckwheat (Fagopyrum esculentum) seeds 90 have been characterized. Evidence indicated that GmMMP2 may play a role in a novel defense mechanism in plants against pathogenic infections.…”
Section: Mmps In Plantsmentioning
confidence: 99%